2021
DOI: 10.1002/clc.23648
|View full text |Cite
|
Sign up to set email alerts
|

Association between the platelet‐lymphocyte ratio and short‐term mortality in patients with non‐ST‐segment elevation myocardial infarction

Abstract: Background Previous studies have shown that inflammation plays an important role in atherosclerosis and cardiovascular disease. Platelet to lymphocyte ratio (PLR) has been reported as a novel inflammatory marker. However, it is not clear whether PLR is associated with short‐term all‐cause mortality in critically ill patients with non‐ST‐segment elevation myocardial infarction (NSTEMI). Methods The data for the study is from the Medical Information Mart for Intensive Care III database. The primary outcome in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…These markers are simple to calculate according to routine blood indicators and have the advantage of being inexpensive and easy to detect, which thus have been used in many clinical studies for early assessment of the prognostic risk of various cardiovascular diseases. 11 , 12 , 13 This study aims to explore the potential connections between inflammation and CHF, and the diagnostic value of systemic inflammatory indicators for CHF.…”
Section: Introductionmentioning
confidence: 99%
“…These markers are simple to calculate according to routine blood indicators and have the advantage of being inexpensive and easy to detect, which thus have been used in many clinical studies for early assessment of the prognostic risk of various cardiovascular diseases. 11 , 12 , 13 This study aims to explore the potential connections between inflammation and CHF, and the diagnostic value of systemic inflammatory indicators for CHF.…”
Section: Introductionmentioning
confidence: 99%
“…13 Also, PLR has been associated with the extent of coronary and carotid artery disease, 24,25 and repeatedly linked to adverse outcomes in ACS patients. 26,27 Further, high PLR was associated with disease severity and longer hospitalizations during the current pandemia in patients infected with SARS-CoV-2. 28,29…”
Section: Discussionmentioning
confidence: 94%
“…13 Also, PLR has been associated with the extent of coronary and carotid artery disease, 24,25 and repeatedly linked to adverse outcomes in ACS patients. 26,27 Further, high PLR was associated with disease severity and longer hospitalizations during the current pandemia in patients infected with SARS-CoV-2. 28,29 Potent platelet inhibition is a mainstay in the pharmacological treatment of patients with atherosclerotic disease, 30 particularly when undergoing stent implantation, and on-treatment residual platelet reactivity has been numerously linked to adverse outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…In cardiovascular disease, Akboga et al showed that PLR was an independent predictor of severe coronary artery disease (OR 1.043 [1.036–1.049], p < 0.001) and determined that an PLR > 109.5 had a sensitivity of 70%, specificity of 58% for predicting the presence of severe coronary atherosclerosis (AUC: 0.708, 95% CI: (0.68–0.73), p < 0.001) [ 16 ]. Meng et al observed that in an acute non-ST-segment elevation myocardial infarction, a PLR ≥ 195.8 was significantly associated with increased 28-day mortality (HR 1.54; 95% CI: (1.09–2.18); p = 0.013) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%